استراتيجية التسيير الأمثل للطاقة لأجل التنمية المستدامة دراسة حالة بعض الاقتصاديات - غانية, نذير (University of Ouargla جامعة ورقلة, 2016)
الملخص: أثبت استغلال مصادر الطاقة التقليدية أنه سلاح ذو حدين، أولها إيجابي يتعلق بدفع عجلة التنمية، أما الثاني فهو سلبي ويتعلق بمشاكل تلويث البيئة. لذا كان لزاما على كل دول العالم أن يخططوا لتنفيذ استراتيجية طاقوية مستدامة ترتكز على محورين أساسيين متلازمين: ترشيد استهلاك الطاقة كمحور أول، والبحث عن مصادر بديلة لهذا النوع من الطاقات كمحور ثاني، بهدف إطالة عمر الطاقة التقليدية من جهة، والحفاظ على البيئة من جهة ثانية، وبالتالي تحقيق نظام طاقة مستدام. وعلى ضوء ذلك، يمكن القول بأن الطاقات المتجددة بديل ممكن للطاقات التقليدية، فهي لا تنضب عكس باقي المصادر التقليدية الأخرى، وعلاوة على ذلك هي طاقات نظيفة لا تؤثر على البيئة، وكما أن الحاجة إليها قد أصبح مطلبا ملحا وأنه لابد من العمل على تطويرها وتنمية استخدامها خلال السنوات القادمة للتمكن من إيقاف التلوث الشديد الحاصل قبل أن يستفحل أمره ويصل إلى حد لا يجدي معه أي علاج. Abstract : It seems that the use of traditional energy sources is a double-edged sword. The first one is positive; related to advancing development. The second is negative, related to the problems of polluting the environment. So it was necessary for all countries of the world to plan for the implementation of sustainable energetic strategy based on two inseparable axes: The first axis is the rationalization of energy consumption, and the second one is seeking for alternative sources for this kind of energy, in order to prolong the traditional energy on the one hand, and the protection of the environment one the other hand. Therefore, a sustainable energy system will be achieved. In light of this, it could be argued that renewable energies can be a possible alternative to the traditional energies. First, they are not inexhaustible like the rest of the other traditional sources. Secondly, they are clean, and do not affect the environment. Finally, the renewable energies become an urgent requirement. Also, it is necessary to work on developing their use in the coming years to be able to reduce the severe pollution before getting worse to the extent that treatment will be in vain.
أطروحة دكتوراه في علوم التسيير تخصص تجارة دولية
Keywords: الطاقة التقليدية، الطاقات المتجددة، استراتيجيات الطاقة، التنمية المستدامة; traditional energy, renewable energies, energy strategies, sustainable development